1984
DOI: 10.1126/science.6729481
|View full text |Cite|
|
Sign up to set email alerts
|

Cell Sensitivity to Gravity

Abstract: Cultures of human lymphocytes exposed in microgravity to the mitogen concanavalin A showed less than 3 percent of the activation of ground controls. This result supports the hypothesis, based on simulations at low g and experiments at high g, that microgravity depresses whereas high gravity enhances cell proliferation rates. The effects of gravity are particularly strong in cells undergoing differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
133
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(142 citation statements)
references
References 2 publications
8
133
0
Order By: Relevance
“…[1][2][3][4][5][6][7] For a long time, it has been clear that microgravity induces alterations in human cells. [8][9][10] However, the corresponding mechanisms are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] For a long time, it has been clear that microgravity induces alterations in human cells. [8][9][10] However, the corresponding mechanisms are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for T lymphocytes, it is known that exposure of cells in culture to actual or modelled low gravity is often accompanied by a major inhibitory effect, remarkably reducing their mitogenic activation process (Cogoli et al 1984) and severely altering growth rate, cytokine production, gene expression, cytoskeletal structures, and motility (for reviews, see Cogoli 1993Cogoli and Cogoli-Greuter 1997;Lewis 2002;Cogoli-Greuter 2004). Furthermore, it has been demonstrated that human lymphocytes are forced to apoptosis in modelled low gravity, through a pathway based on calciumdependent 5-LOX activation, mitochondrial membrane disruption, and cytochrome c release, followed by caspase activation and cell death (Maccarrone et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations conducted in space laboratories and with instruments averaging the gravity vector, and thus simulating conditions of reduced gravity, have shown that isolated cells may change their behavior under altered gravitational conditions. Loss of cell activation [Cogoli et al, 1984], perturbation of signal transduction [Schmitt et al, 1996;Hashemi et al, 1999] and modification of genetic expression [Walther et al, 1998;Hammond et al, 1999] have been described. This suggests that some of the mechanisms at the roots of the systemic effects observed in weightlessness, such as depression of the immune system [Gmü nder and Cogoli, 1996] …”
Section: Introductionmentioning
confidence: 99%
“…Several investigations conducted in space laboratories and with instruments averaging the gravity vector, and thus simulating conditions of reduced gravity, have shown that isolated cells may change their behavior under altered gravitational conditions. Loss of cell activation [Cogoli et al, 1984], perturbation of signal transduction [Schmitt et al, 1996;and reduction in bone mass [Morey-Holton et al, 1996], can originate at the cellular level.…”
mentioning
confidence: 99%